Ambiguïtés et limites de la transition énergétique en Allemagne - Michel Deshaies (VertigO)
The energy transition is the basis of the German energy policy means a policy of reducing consumption and substitution of renewable energy to fossil fuels. Germany is one of the countries with the most highly developed renewable energy providing 25% of the total electricity production. However, as and when the share of renewables increases, many problems appear and amplify. Problems with the acceptability of increasingly large wind turbines have emerged with the massive development of wind energy. But the main limitations to the development of renewable energy come from a part of the location of production areas to the main consumption areas and secondly from their intermittent and unpredictable production which greatly complicates their integration into the electrical system. There is a significant imbalance between northern Germany where the largest wind generation capacity is located and Rhenish and South Germany, where electricity consumption is higher due to the concentration of population and industries. The need to compensate for fluctuations in power generation of renewables imposes a long time to have a fleet of power plants with a high-emitting of carbon dioxide. To increase continuously the production capacity of renewables, without having storage capacity through pump storage hydropower, can only lead to amplify these problems and can be solved only at european level.